Gaming for Peace: Gender Awareness Training and the Polish Military - Holohan, Anne (My University, 2018)
Despite regulatory and legal changes, women are persistently underrepresented in military organisations on peacekeeping missions. This article argues that part of the reason for this can be found in persistent stereotypical ideas about gender roles, and looks at the attitudes and experience of Polish military personnel who have been deployed on peacekeeping missions as evidence of this. However, witnessing other militaries stance on gender, where such stereotypes are still there, but not as entrenched, can cause personnel to contextualise if not question their own organisation’s stance on gender. Sixteen Polish military peacekeepers were interviewed in-depth about their experiences on peacekeeping missions as part of a European H2020 project, Gaming for Peace (GAP). The interviews were used to build scenarios for a digital role-playing game to develop soft skills among peacekeeping personnel, and these soft skills included gender awareness. Th is article analyses the interviews to explore the experience of gender for both men and women in the Polish military, and shows that there is an urgent need for the type of training in gender awareness that is part of GAP.
PUBLISHED
Keywords: peacekeeping, pre-deployment training, women, gender awareness, stereotypes